Nursing care to the patient with venous ulcer: integrative review - Vieira, Marcos Israel dos Santos (2021)
Introduction: Venous ulcers are defined as chronic lesions in the lower limbs, being more common in the legs. Individuals with chronic ulcers in the lower limbs have a significant impact on their quality of life arising from the problem of chronic injuries. Objective: Describe the scientific evidence available in the literature on nursing care for patients with venous ulcers. Methods: This is an integrative literature review, from 2016 to 2021, in the Lilacs and BDENF databases. The following descriptors were used in the bases: “Varicous Ulcer”, “Nursing”, “Nursing Care”. For the crossing of descriptors, a protocol with Boolean AND was used. As inclusion criteria, articles available in the databases and with full text and open access and studies available in Portuguese were selected. Exclusion criteria were editorials from journals, letters to the editor and studies that did not address the theme of the work. Results: After filtering based on the defined flowchart, ten articles were selected according to established criteria. After reading and analyzing the articles, two thematic categories emerged, which were: “Nursing Care in Venous Ulcer” and “Nursing Care Management”. Conclusion: it is concluded that the control of non-communicable chronic diseases associated with the use of dressings and pain management are essential in the treatment of venous ulcers.